The Implementation of Cash Waqf as a Social Financial Instrument in Indonesia - R Suhaimi; Sri Fatimah Rahmatillah; Baidawi Arrohman; Mutia Pamikatsih; Jodang Setia Adi Anista R (International Conference on Islamic Economic (ICIE), 2026)
Waqf is one of the important instruments of Islamic social finance that contributes to social welfare, economic development, and sustainable community empowerment. Along with the development of financial technology and the increasing demand for innovative Islamic financial products, the implementation of waqf in Indonesia has expanded beyond traditional forms of land and property to include cash-based instruments. This research aims to identify the implementation of waqf as one of the Islamic social finance instruments in Indonesia. The study employs a qualitative literature review method by analyzing relevant books, journal articles, regulations, and institutional reports related to waqf practices in Indonesia. The findings reveal that cash waqf represents a contemporary form of waqf implementation that has significantly developed within the Indonesian Islamic finance ecosystem. In the Indonesian context, the Indonesian Ulema Council (MUI) officially authorized cash waqf through its fatwa issued on May 11, 2002, providing a legal and religious foundation for its implementation. Cash waqf is currently practiced through several mechanisms, including direct cash donations, stock or securities waqf, and digital waqf platforms. Its implementation involves collaboration among Islamic Financial Institutions (LKS), halal marketplaces, waqf management institutions, and other social organizations. These developments demonstrate that cash waqf has become an innovative and accessible instrument with significant potential to strengthen Islamic social finance and promote inclusive socio-economic development in Indonesia.